EFEKTIVITAS E-MODUL LARUTAN PENYANGGA BERBASIS PROBLEM BASED LEARNING TERINTEGRASI TEACHING AT THE RIGHT LEVEL TERHADAP HASIL BELAJAR PESERTA DIDIK FASE F SMA - Fauziah, Ivo; Iryani, Iryani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
Buffer solutions are a topic taught in the even semester of Grade XI Phase F in Indonesian senior high schools (SMA/MA). This subject is inherently complex and involves extensive mathematical calculations, often making it difficult for students to comprehend. Based on interviews with teachers and a questionnaire distributed to students at the UNP Laboratory Development Senior High School, it was found that 87% of students reported difficulty in understanding the concepts of buffer solutions. The instructional materials used were limited to printed formats and failed to capture students attention. One of the key components of successful learning is the quality of instructional materials provided to students. Therefore, a buffer solution e-module based on Problem-Based Learning (PBL) integrated with the Teaching at the Right Level (TaRL) approach was implemented. Although this e-module had undergone validation for content quality and practicality, its effectiveness had not yet been tested, and as such, it was not ready for widespread adoption. The purpose of this study was to evaluate the effectiveness of the buffer solution e-module based on PBL integrated with TaRL in improving student learning outcomes. The research employed a pre-experimental method using a one-group pretest-posttest design. The sample consisted of 30 students from Grade XI F5, selected using purposive sampling. The instrument used in this study was a multiple-choice test that met criteria for validity, discriminating power, reliability, and appropriate difficulty level, indicating good item quality. Data analysis yielded an N-Gain score of 0.713, which falls into the high category. The statistical analysis of the hypothesis test using the paired sample t-test yielded a calculated t-value of 19.489 > table t-value of 1.699. Based on these findings, it was proven that the e-module on buffer solutions based on PBL integrated with TaRL is effective in improving student learning outcomes. ABSTRAKLarutan penyangga merupakan salah satu materi yang dipelajari pada kelas XI Fase F SMA/MA semester genap. Materi ini bersifat kompleks dan banyak menggunakan perhitungan matematika sehingga seringkali dianggap sulit oleh peserta didik. Berdasarkan hasil wawancara guru dan penyebaran angket peserta didik di SMA Pembangunan Laboratorium UNP didapatkan data bahwa 87% peserta didik mengalami kesulitan dalam memahami konsep dari materi larutan penyangga. Bahan ajar yang digunakan masih sebatas bahan ajar cetak dan kurang menarik perhatian peserta didik. Salah satu komponen keberhasilan pembelajaran ditentukan oleh kualitas bahan ajar yang diberikan kepada peserta didik. Untuk itu, dilakukan pembelajaran dengan menggunakan e-modul larutan penyangga berbasis Problem Based Learning terintegrasi Teaching at The Right Level. E-modul larutan penyangga ini telah diuji validitas dan praktikalitasnya, namun belum melalui uji efektivitas sehingga belum dapat digunakan secara luas. Penelitian ini bertujuan untuk mengetahui tingkat keefektifan e-modul larutan penyangga berbasis Problem Based Learning terintegrasi Teaching at The Right Level terhadap hasil belajar peserta didik. Penelitian ini dilakukan dengan menggunakan metode pra-eksperimental dengan desain penelitian one-group pretest-posttest design. Sampel penelitian ini berjumlah 30 orang peserta didik kelas XI F 5 yang dipilih menggunakan teknik purposive sampling. Instrumen yang digunakan dalam penelitian berupa tes pilihan ganda yang memiliki validitas, daya pembeda, reliabilitas dan indeks kesukaran dengan kriteria soal baik. Data hasil analisis didapatkan nilai N-gain sebesar 0,713 dengan kategori tinggi dan hasil analisis statistik uji hipotesis menggunakan uji paired sample t-test, didapatkan hasil thitung 19,489 > ttabel 1,699. Berdasarkan temuan tersebut terbukti bahwa e-modul larutan penyangga berbasis PBL terintegrasi TaRL efektif meningkatkan hasil belajar peserta didik.